The Correlation between Anti-Mullerian Hormone Levels and The Number of Oocyte Retrieved and Pregnancy Rate in Infertile Women Who Underwent IVF in Makassar City - Estiastuti, Arini; Abdullah, Nusratuddin; Butje Leonardy, Rudy (International Journal of Psychosocial Rehabilitation, 2020)
Anti-Mullerian hormone (AMH) being a good marker for ovarian response. Decreased serum AMH levels may be indicative for poor response in vitro fertilization (IVF) in women with a diminished ovarian reserve This study aims to determine the serum level of AMH correlation with the number of oocyte retrieved and pregnancy rate in infertile women. This cross-sectional study was eligible for 254 infertile women who underwent in vitro fertilization in private IVF Clinic in Makassar. AMH serum levels were measured on cycle day 3. The number of oocytes were determined on the day of oocyte retrieval. Pregnancy was determined by the β- hCG test on day 16 of the cycle. Serum AMH levels show a significant negative correlation with women .05). The AMH levels and the number of oocytes retrieved might predict the ovarian function. AMH levels could not predict the pregnancy rates.